Gene microarray analysis revealed a potential crucial gene RACK1 in oral squamous cell carcinoma (OSCC). Issue 2 (4th March 2018) - Zheng, Jian-Wei; Yang, Yinshen; Yang, Shujuan; Zhou, Wei; Qiu, Hongtian; Li, Xiaoping; Cai, Qiuyun; Li, Ting; Luo, Gang
ABSTRACT: Oral squamous cell carcinoma (OSCC) is the sixth most common cancer worldwide, which appears as a consequence of multiple molecular genetic events in various chromosomes and genes. In order to unveil the possible mechanisms underlying OSCC tumorigenesis, the OSCC-related gene expression variance and the gene interaction network should be further investigated. Herein, we conducted the NimbleGen Human Gene Expression Microarray to analyze expression heterogeneity between OSCC primary tumor tissue and its adjacent normal tissue from two patients. A total number of 7872 out of 32, 448 detected genes are differentially expressed in OSCC. Gene ontology (GO) analysis demonstrated that these differentially expressed transcripts were critical in a series of metabolic processes, cancer-related signal pathways, and biological regulations. KEGG signaling pathway enrichment suggested a number of pathways (metabolic process and immune response) which are frequently enrolled during cancer progression. 15 most differential regulated genes between OSCC tumor and non-tumor were confirmed by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Furthermore, the interaction network analysis of these confirmed genes by STRING database showed the two subunits of RACK1 had direct interaction with 14 differential proteins. This bioinformatics research lends support about the critical role of RACK1 which functions as a key node protein driving OSCC development.